PENERAPAN GOOD CORPORATE GOVERNANCE (Tinjauan Manfaat, Kendala, Tantangan dan Kesempatan Bagi Perusahaan Publik di Indonesia) - Dwiridotjahjono, Jojok (FIA UB, 2008)
Abstract Corporate governance is still at the top of the agenda for Indonesia and Asian corporations. The issue of corporate governance arises since economic crisis in Indonesia and Asian countries. Country factors can play a key role in setting the framework for corporate governance practices at the individual company level. Given that corporate governance matters regardless of the particular system — the legal and economic framework conditions — investors have shown growing interest in a global benchmark of good behavior There persists the belief that good corporate governance can help create shareholders value and ensuring that enterprises only responsibility to society is to maximize profits without breaking the law, hence the role of corporate governance is to provide appropriate corporate control. This article elaborated about implementation good corporate governance; benefits, obstacles, challenge and opportunity for Indonesia corporations. Keywords: Good Corporate Governance, accountable, responsible, independent, fairness